2010
DOI: 10.1021/es1007966
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Reactive Aromatics As a Major Source of Peroxy Acetyl Nitrate over China

Abstract: We analyze the observations of near-surface peroxy acetyl nitrate (PAN) and its precursors in Beijing, China in August of 2007. The levels of PAN are remarkably high (up to 14 ppbv), surpassing those measured over other urban regions in recent years. Analyses employing a 1-D version of a chemical transport model (Regional chEmical and trAnsport Model, REAM) indicate that aromatic non-methane hydrocarbons (NMHCs) are the dominant (55-75%) PAN source. The major oxidation product of aromatics that produces acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 51 publications
10
95
2
Order By: Relevance
“…Peroxyacetyl radical, as an important component of peroxy radicals, also participates in O 3 production, and generates PAN via its reaction with NO 2 in the atmosphere. Therefore, a positive correlation between PAN and O 3 is expected and has been reported in the summer and autumn daytime in Beijing (Liu et al, 2010;Wang and Zhang, 2007; 2009) and in other urban areas, i.e., Porto Alegre, Brazil (Grosjean et al, 2002) and Munich .…”
Section: Correlation Between Pan and Omentioning
confidence: 72%
See 1 more Smart Citation
“…Peroxyacetyl radical, as an important component of peroxy radicals, also participates in O 3 production, and generates PAN via its reaction with NO 2 in the atmosphere. Therefore, a positive correlation between PAN and O 3 is expected and has been reported in the summer and autumn daytime in Beijing (Liu et al, 2010;Wang and Zhang, 2007; 2009) and in other urban areas, i.e., Porto Alegre, Brazil (Grosjean et al, 2002) and Munich .…”
Section: Correlation Between Pan and Omentioning
confidence: 72%
“…Due to the particular importance of PANs on atmospheric chemistry, a great number of PANs measurements have been conducted intensively in developed countries, including the urban regions (Grosjean et al, 2001;Marley et al, 2007;Roberts et al, 1995) and remote area (Hartsell et al, 1994;Roberts et al, 2004;Singh et al, 1990Singh et al, , 1992Williams and Grosjean, 1991). However, only few researches involving with PANs are implemented in developing countries of Asia (Lee et al, 2008;Watanabe et al, 1998;Zhang and Tang, 1994;Wang et al, 2010;Zhang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1f showed that PAN observations were underestimated by more than 80% in both Cases R and E. It is likely because the model underestimated the concentrations of acetaldehyde (CH 3 CHO) and methylglyoxal (MGLY, CH 2 CHC(O) CH 3 ) (Fig. S2), which were found as the dominant PAN sources in urban Beijing (Liu et al 2010). The additional HONO sources also increased daytime concentrations of CH 3 CHO, MGLY and PAN.…”
Section: New Parameterization Of Honomentioning
confidence: 98%
“…For winter period, only 24-h averages of HONO, NO 2 and NO 3 − were obtained. Details were given in Liu et al (2010) and Spataro et al (2013).…”
Section: Observed Datamentioning
confidence: 99%
“…Photochemical pollution has become an important air quality issue in China due to increased emissions of volatile organic compounds (VOCs) and nitrogen oxides (NO x ) driven by the rapid economic growth (Liu et al, 2010). Aldehydes, an important class of VOCs, are directly discharged into the troposphere from biogenic and anthropogenic sources (Zhang et al, 2006b), and have received scientific and regulatory attention due to their potential adverse health effects on humans as well as their important role in atmospheric photochemical reactions (Grosjean, 1982;Hoekman, 1992;Nondek et al, 1992;Zhou and Mopper, 1990).…”
Section: Introductionmentioning
confidence: 99%